13.7% Efficiency Small‐Molecule Solar Cells Enabled by a Combination of Material and Morphology Optimization. Issue 51 (6th November 2019) - Yue, Qihui; Wu, Hao; Zhou, Zichun; Zhang, Ming; Liu, Feng; Zhu, Xiaozhang
Abstract: Compared with the quick development of polymer solar cells, achieving high‐efficiency small‐molecule solar cells (SMSCs) remains highly challenging, as they are limited by the lack of matched materials and morphology control to a great extent. Herein, two small molecules, BSFTR and Y6, which possess broad as well as matched absorption and energy levels, are applied in SMSCs. Morphology optimization with sequential solvent vapor and thermal annealing makes their blend films show proper crystallinity, balanced and high mobilities, and favorable phase separation, which is conducive for exciton dissociation, charge transport, and extraction. These contribute to a remarkable power conversion efficiency up to 13.69% with an open‐circuit voltage of 0.85 V, a high short‐circuit current of 23.16 mA cm −2 and a fill factor of 69.66%, which is the highest value among binary SMSCs ever reported. This result indicates that a combination of materials with matched photoelectric properties and subtle morphology control is the inevitable route to high‐performance SMSCs. Abstract : An ideal materials combination based on the electron donor BSFTR and acceptor Y6 is selected to construct small‐molecule solar cells (SMSCs). By morphology optimization, an extraordinary power conversion efficiency of 13.69% with a remarkably low energy loss of 0.48 eV is achieved, which is beneficial from the matched photoelectric properties and the favorable blend morphology, and is the best binary SMSC performance reported so far.